Status gizi dan gambaran klinis penyakit pada pasien HIV anak awal terdiagnosis - Ratni Indrawanti; Egi Arguni; Ida Safitri Laksanawati; Dwiyanti Puspitasari; Dominicus Husada (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2021)
Nutritional status and clinical disease of HIV children patients when diagnosed for the first timeBackground: Human immunodeficiency virus (HIV) infection in children can cause nutritional problems. Currently, HIV-infected children are still diagnosed when the disease stage is advanced. Nutritional status is a marker of advanced stage conditions in HIV infection.Objective: To determine the clinical findings of disease and nutritional status of HIV children patients when diagnosed for the first time.Methods: We conducted a cross-sectional descriptive study. The data were taken from the medical record documents of child patients aged 0-18 years with the ICD 10 code B20, who was treated at the Dr. Sardjito Yogyakarta Hospital from 1 January 2004-31 December 2019. Results: There were 191 children diagnosed with HIV, 56% of them were boys. The median age was 34 months (IQR 25: 13 months, IQR 75: 69 months), and 95.5% among those were infected perinatally. There were 77 (40,3%) children who suffered from severe malnutrition and 55 (28.8%) children were moderate acute malnutrition. At the age of 0-60 months among them, there were 49 children (36.3%) suffered from severely underweight, 35 children (25.9%) underweight, 53 (39.3%) severely stunted, 38 (28.1%) stunted, 28 severely wasted (20.7%), and wasted as many as 24 (17.8%). At the age of 5-18 years old, there were 19 (33.9%) and 5 (8.9%) children who suffered from severely wasted and wasted respectively. World Health Organization (WHO) stages 3 and 4 were experienced by 62 (32.5%) and 68 (35.6%) children. As many as 41.3% of children had enlarged lymph nodes, thrush (40.8%), pneumonia (40.8%), and persistent or chronic diarrhea (21.5%). Conclusions: The nutritional status of HIV-infected children at baseline was dominated by underweight and stunted. The most clinical findings of the disease when the child was diagnosed with HIV infection were lymphadenopathy, oral thrush, pneumonia, and persistent or chronic diarrhea.